Petrology of UHP eclogite-facies felsic schist in the Western Tianshan subduction zone, China - Zhang, Lijuan; Zhang, Lifei; Qi, Ning; Bader, Thomas (Frontiers in Earth Science, 2023)
Although quartzo-feldspathic metasedimentary rocks are widespread in high pressure-ultrahigh pressure (HP-UHP) metamorphic belts worldwide, their petrogeneses and metamorphic evolutions are poorly understood. We discovered an UHP eclogite-facies felsic schist in the Western Tianshan metamorphic belt, China. Petrological observations and phase equilibria modeling both indicate the felsic schist experienced UHP metmorphism in the coesite stability field. In particular, it experienced prograde metamorphism at 21–24 kbar, 445–470°C, a pressure peak at 25-28 kbar and 490–525°C, and eventually heating with decompression to 20 kbar and 560°C. The obtained clockwise P–T path is consistent with those of other lithologies (eclogite and pelitic schist) from the same belt, which provides new evidence for the coherent exhumation of the UHP unit of the Western Tianshan metamorphic belt. The final uplift of the Western Tianshan oceanic crust to the surface is attributed to fluid activity and the late tectonic deformation.